Psychological Responses to Violations of Expectations: Perspectives and Answers from Diverse Fields of Psychology - Anna Thorwart (Frontiers Research Topics, 2018)
From Pavlov's dog expecting food when hearing a bell to stereotypes as expectations about other people's behaviour, from Bandura's self-efficacy as expectation for success and failure of one's own behaviour to the "predictive brain" concept in current perception theories: expectations have been a central construct in different areas of psychological research. In each of these areas, specific concepts, theoretical approaches, and empirical methods have been developed to explain when and why expectations persist and when they do not. Many theories assume that expectations are likely to change in the face of disconfirming evidence. However, sometimes expectations persist even though they are empirically violated, suggesting that they can be "sticky" under certain circumstances. But what are these circumstances? And what are the psychological mechanisms that can explain why and when expectations persist or change after being confronted with expectation-violating evidence? Each contribution of the current book offers insights into individuals' reactions to violations of expectations. They show that many pieces of the puzzle have been collected in the many sub-displiclines of psychology and that putting them together in an integrative fashion stays a fascinating enterprise.